Generation of 3D ex vivo mouse- and patient-derived glioma explant slice model for integration of confocal time-lapse imaging and spatial analysis - Andrea Comba; Maria Luisa Varela; Syed M. Faisal; Clifford C. Abel, II; Anna E. Argento; Wajd N. Al-Holou; Todd C. Hollon; Jacqueline D. Perelman; Patrick J. Dunn; Sebastien Motsch; Maria G. Castro; Pedro R. Lowenstein (STAR Protocols, 2023)
Summary: Development of spatial-integrative pre-clinical models is needed for glioblastoma, which are heterogenous tumors with poor prognosis. Here, we present an optimized protocol to generate three-dimensional ex vivo explant slice glioma model from orthotopic tumors, genetically engineered mouse models, and fresh patient-derived specimens. We describe a step-by-step workflow for tissue acquisition, dissection, and sectioning of 300-μm tumor slices maintaining cell viability. The explant slice model allows the integration of confocal time-lapse imaging with spatial analysis for studying migration, invasion, and tumor microenvironment, making it a valuable platform for testing effective treatment modalities.For complete details on the use and execution of this protocol, please refer to Comba et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.